Ballet movements in rhythmic gymnastics routines: an analisys from the last two code of points (2013-2016 and 2017-2020) - Nabanete dos Reis Furtado, L.; de Toledo, E.; Fernandes Antualpa, K.; Carbinatto, M. V. (Science of Gymnastics Journal, 2020)
Ballet is a world-renowned dance and its movements can be seen in athletes` education and training systems from various sports, especially those considered artistic sport, such as rhythmic gymnastics (RG). The competition system of this sport is driven by a Code of Points (CoP) that is established every four years and, although it has some changes during the years, remains in its essence clearly influenced by dance aspects as well as Ballet movements in its performance. Thus, the purpose of this research was to analyze the Ballet movements in RG routines in the 2013-2016 and 2017-2020 Olympic cycles, in order to further understand the relationship between RG and Ballet and compare them in two different RG Code of Points. This was a quantitative research that analyzed 24 RG routines performed at RG World Championship (2013 and 2019) recorded and posted at one of the International Gymnastics Federation`s official social media websites. Results show that: a. there was no significant difference between the years (p = 0,05), but the average of Ballet movements in the four apparatus routines in 2013 was higher than 2019; b. although the difference was not significant, the analysis of the magnitude of the effect size showed a small difference for ball (0.68) and clubs (0.29) and moderate for hoop (0.97) and ribbon (0.74); c. Ballet movements performed during Apparatus Difficulties (AD) and Dynamics Elements of Rotation (R) increased; those performed as connecting elements decreased.